An Exploration of Working Capacity and Return to Work after Cerebrovascular Accident - McCaffer, Kieran (2023)
This portfolio contains three parts. Part one is a systematic literature review, in which the empirical literature concerning the psychological and neuropsychological comorbidities related to working capacity following stroke is reviewed. Part two is an empirical paper, which investigates the potential mediating effect of illness perceptions on the association between degree of comorbidities and post-stroke work status. Part three comprises the appendices.
Keywords: Clinical psychology